Crisis management system at a Thai telecommunication company : a case study of UCOM (Network) - Sukanya Thongserm; Do, Ba Khang; Truong, Quang; Tang, John C.S.; United Communication Industry Public Company Limited (UCOM) (Bangkok : Asian Institute of Technology, 1998)
Since July, 1997, Thailand has faced the economic crisis situation. It has affected many business areas, especially in the businesses which deal with the exchange foreign currencies. Telecommunication industry is also the one who has affected from this crisis. Some companies have to cease their businesses and some have to find the solutions to survive. Establishment the crisis management system in organization is one of wise solution to cope with the crisis. However, there are many crisis management systems provided during global change. The company who wants to carry out this system should deliberately consider whether it fit with the company or not. For the case company, UCOM (Network), we have selected the crisis management model of Nunamaker, Weber, and Chen to be the framework. The analysis presented the crisis management system of case company based on the selected model. However, there are both the benefits and limitations of adapting this model to the case company. The top management should weight the positive and negative outcomes before proceeding.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1998
Keywords: Telecommunication -- Thailand